2008
DOI: 10.1002/aic.11538
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of fines deposition in an alternating semifluidized bed

Abstract: in Wiley InterScience (www.interscience.wiley.com).A semifluidized bed was proposed to allay bed plugging during the filtration of fines-hydrocarbon suspensions. Mitigation of plugging was allowed by alternating semifluidization during capture with unconstrained fluidization for removal of deposits. Solids holdup conditions were established to prevent deposition in the fluidization section. The cyclic parameters were varied to allow efficient removal of deposits during washing. Analysis with a filtration model… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…14 shows the comparison of the values of (h − h s )/(h − h pa ) predicted from Eqs. (14)- (17) with the experimental ones. Almost all values are within 15% of the experimental ones in case of these equations.…”
Section: Packed Bed Formationmentioning
confidence: 93%
See 1 more Smart Citation
“…14 shows the comparison of the values of (h − h s )/(h − h pa ) predicted from Eqs. (14)- (17) with the experimental ones. Almost all values are within 15% of the experimental ones in case of these equations.…”
Section: Packed Bed Formationmentioning
confidence: 93%
“…Subsequently a good number of research articles relating to various applications of the semi-fluidized bed system have been reported in literature [3][4][5][6][7][8][9][10][11][12][13][14]. Additionally, fairly a good number of patents claimed since the year 1958, relating to the best possible applications of the semi-fluidized bed in many industrial processes are listed in SciFinder Scholar database like the recent one by Liu et al [15].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies reported that the pressure drop in a hydrotreater increased with the concentration of the fine particles. 34…”
Section: Discussionmentioning
confidence: 99%
“…Also, higher pressure that is statistically shown to decelerate the bed deposition in the case of feed with high fines concentration might be compensating the pressure drop in the reactor due to catalyst pore plugging. Several studies reported that the pressure drop in a hydrotreater increased with the concentration of the fine particles …”
Section: Discussionmentioning
confidence: 99%
“…Some of the early semifluidized bed applications concerned biological systems in which the fluidized layer, exhibiting the highest backmixing, carries the main load of biological reaction, whereas the top packed bed acts as a polishing section. Recently, Dehkissia et al studied the filtration behavior in an alternating bed, switching between semifluidization and fluidization for oil sand application.…”
Section: Introductionmentioning
confidence: 99%